PENGARUH DISTRIBUSI BAHAN POKOK TERHADAP KEPUASAN PELANGGAN - Kaparang, Gratia Natrina (JURNAL ADMINISTRASI PUBLIK, 2014)
Gratia Natrina Kaparang, 100812002, Majors Administration Program Study Administration Business, April 2014 " On The Influence Of Distribution Materials To Satisfaction of Consumerâ€™s (Study at Costumer/ client] of Nimble Shop exist in Sub-Province of Minahasa South-East)". Guided By : Dr. Drs. J. R. E. Tampi, M.Si and of Drs. Harry J. Sumampouw, M.Si. ABSTRACT The activity of distribution for the everlasting business of some coorporate business is very important. That is why this activity has to be carried on to satisfy the consumers needs, also to hold the consumers stay on. Then, the material is primary for the sustainebleness of menâ€™s life. Therfore, the writte check and understand how important the distribution to serve the consumers needs for the sakeness of giving satisfaction to the consumers. In relation to what is said above, we formulate the problem such as : Is the material distribution influenced towards the consumers satisfaction? The theory of marketing strategy and theory of distribution as well as the theory of consumers satisfaction explain the problem above by hypothesis as follow : there is an influence of the material distribution towards the consumers satisfaction. To test the hypothesis, we do the research based on the descriptive-quantitative method. The samples the simple coorelation technique and the simple linear-regression technique. Test significant shows by reality that r â‰  0, so that Ho refused and Ha is accepted in the level of significancy of 95%. The Significant test is ï¢ â‰  0, then Ho refused and Ha formulated aas coeficient regression (b = ï¢1) is significant. This result strengh then the Saladinâ€™s view (2006) and also Wellingtonâ€™s view (1998). Conclusion of this research is: 1) Distribution variable have influence and relation which is signifikan to satisfaction of consumer so that thereby activity of distribution have to be taken care of and continue to be developed by for the shake of taking care of satisfaction of consumer; 2) Activity of distribution not merely focussed at sale of just goods, but require to pay attention requirement and character each;every consumer so that can maintain consumer satisfactorily what becoming requirement each;every consumer; 3) Each;Every employees employed by company have to comprehend the target of company in gratifying consumer so that can cooperate in reaching the target.Keyword : Materials Distribution, Consumerâ€™s Satisfaction.